PRESENTATION INFORMATION PROFILE PT. MAIN PERKASA THROUGH SELF INTENET USING MACROMEDIA FLASHMX - Suhardianto Suhardianto; Ir. Fitri Sjafrina (Jurnal Sistem Informasi, 2006)
Internet as information resources that reach the entire world is information on currentdevelopments. Such information can be presented through the web, and this web canbe more interesting if there is animation or design with a more lively appearance.PT. MAIN MANDIRI PERKASA in developing their business, hence made aninteresting website with animation and design look more alive.